Transplanting and the addition of boron in sweet corn (Zea mays L. group saccharate) production = Trasplante y adición de boro en la producción de maíz dulce (Zeamays L. grupo saccharate) - Al Shammari, Aziz Mahdi Abd; Hamdi, Ghassan Jaafar; Najm Abdullah, Solieman Daowd (2022)
Introduction. Low seedbed temperatures at the planting and the direct sowing method can reduce the sweet corn germination. Transplanting may offer optimum environmental conditions for seed germination, early crop maturity, and increase sweet corn (Zea mays L. group saccharata) productivity. Boron deficiency depresses sweet corn yield through male sterility. Objective. To evaluate the effect of transplanting and the addition of boron in sweet corn production. Materials and methods. A field experiment was conducted from March 19 to June 20, 2020 at the Research Station of Horticulture Department and Landscape Gardening Architecture, University of Diyala, Baqubah, Iraq. Direct sowing and transplanting, and foliar application of boron at 0, 50, or 75 mg L-1 was evaluated to determine effects on the yield, the yield components, and water use efficiency of sweet corn cultivars: Roi Soleal, Seker misir, and Succar. Results. The cv. Seker Misir matured faster (57.5 days), had wider ears (4.53 cm), more kernel rows (16.0), the highest kernel yield (6.00 t ha-1), and a higher water use efficiency (WUE) (2.85 kg m-3). The cv. Succar had the longest ears (18.48 cm) and the heaviest fresh ears (251 g). Transplanting hastened the time to maturity (54.18 days), and produced the longest ears (17.91 cm), widest ears (4.52 cm), most kernel rows (15.96), heaviest fresh ears (229 g), the highest kernel yield (5.56 t ha-1), and the highest WUE (2.64 kg m-3). The 50 mg L-1 fertilizer treatment produced the longest ears (17.61 cm), widest ears (4.58 cm), more kernel rows (16.61), the highest kernel yield (5.64 t ha-1), and the highest WUE (2.68 kg m-3). The least time to maturity (57.72 days) and heaviest fresh ears (232 g) occurred with 75 mg L-1 of boron fertilizer. Conclusion. The use of 50 mg L-1 boron, as a foliar fertilizer, appears to be, next to the transplanting method, suitable for the cultivation of sweet corn plants to increase productivity and WUE.
Introducción. Las bajas temperaturas del semillero en la plantación y el método de siembra directa pueden reducir la germinación del maíz dulce. El trasplante puede ofrecer condiciones ambientales óptimas para la germinación de la semilla, una madurez temprana del cultivo y un aumento de la productividad del maíz dulce (Zea mays L. grupo saccharata). La deficiencia de boro reduce su rendimiento por la esterilidad masculina. Objetivo. Evaluar el impacto de los métodos de siembra y la aplicación de boro en cultivares de maíz dulce. Materiales y métodos. Se realizó un experimento de campo del 19 de marzo al 20 de junio de 2020 en la Estación de Investigación del Departamento de Horticultura y Arquitectura de Jardinería Paisajista de la Universidad de Diyala, Baqubah, Irak. Se evaluó la siembra directa y el trasplante, y la aplicación foliar de boro a 0, 50 o 75 mg L-1, para determinar los efectos en el rendimiento, los componentes del rendimiento y la eficiencia en el uso del agua de los cultivares de maíz: dulce Roi Soleal, Seker misir y Succar. Resultados. El cv. Seker Misir maduró más rápido (57,5 días), tuvo mazorcas más anchas (4,53 cm), más hileras de granos (16,0), el mayor rendimiento de granos (6,00 t ha-1) y una mayor eficiencia en el uso del agua (WUE) (2,85 kg m-3). El cv. Succar mostró las mazorcas más largas (18,48 cm) y las mazorcas frescas más pesadas (251 g). El trasplante aceleró el tiempo hasta la madurez (54,18 días) y produjo las mazorcas más largas (17,91 cm), las más anchas (4,52 cm), la mayoría de las hileras de granos (15,96), las mazorcas más pesadas (229 g), el mayor rendimiento de granos (5,56 t ha-1) y una mayor WUE (2,64 kg m-3). El tratamiento con 50 mg L-1 de fertilizante produjo las espigas más largas (17,61 cm), las espigas más anchas (4,58 cm), más hileras de granos (16,61), el mayor rendimiento de granos (5,64 t ha-1) y el WUE más alto (2,68 kg m-3). El menor tiempo hasta la madurez...
En Revista Agronomía mesoamericana
Volumen 33, número 1 (enero - abril 2022)
Descripción basada en el contenido visto el 26 de Octubre, 2023
También disponible en formatos EPUB, HTML, XML y MP3 (español e ingles)
Keywords: MAIZ -- CULTIVO; FERTILIZACION FOLIAR; BORO; TRASPLANTE (PLANTAS CULTIVADAS); GERMINACION; EXPERIMENTOS DE CAMPO (AGRICULTURA)